2004
DOI: 10.1098/rspb.2004.2719
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diet switching on resource allocation to reproduction and longevity in Mediterranean fruitflies

Abstract: Understanding the factors that determine the allocation and utilization of organism resources may provide an insight into the mechanisms of adaptation, ageing and reproduction. Resource allocation, which is regarded as a method of adaptation, increases fitness and is genetically controlled. Experiments with variable diet feeding of female Mediterranean fruitflies (Ceratitis capitata) demonstrated that the feeding regime dramatically influences lifespan, mortality and the reproduction of flies. An analysis of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…The absence of proteins in the adult food diet both delayed the ovarian maturation and decreased the fecundity of females. Similarly, Romanyukha et al (2004) and Nestel et al (2005) reported that the access to protein food sources significantly influences egg production and longevity in the Mediterranean fruit fly, C. capitata . Manrakhan and Lux (2006) , comparing three natural food sources, showed that fecundity was higher when Ceratitis fasciventris (Bezzi) and C. capitata females were fed on a protein-rich diet.…”
Section: Infl Uence Of Adult and Larval Dietsmentioning
confidence: 91%
“…The absence of proteins in the adult food diet both delayed the ovarian maturation and decreased the fecundity of females. Similarly, Romanyukha et al (2004) and Nestel et al (2005) reported that the access to protein food sources significantly influences egg production and longevity in the Mediterranean fruit fly, C. capitata . Manrakhan and Lux (2006) , comparing three natural food sources, showed that fecundity was higher when Ceratitis fasciventris (Bezzi) and C. capitata females were fed on a protein-rich diet.…”
Section: Infl Uence Of Adult and Larval Dietsmentioning
confidence: 91%
“…Consequently, adult diet should have an important effect on life‐history schedules and this has been well‐documented in many species (Tatar & Carey 1995; Chapman & Partridge 1996; Hunt et al . 2004b; Romanyukha et al . 2004; Hunt et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Romanyukha et al. ; Davies et al. ) and the mechanistic underpinnings involved (e.g., the insulin and rapamycin pathways; Neufeld ; Partridge et al.…”
mentioning
confidence: 99%